(untitled) (Global Journal of Medical Research, 2018)
The intensity of free-radical processes (SRP) and the activity of antioxidant systems (AOS) in the saliva and plasma of people with pathology of the pathobiliary system were studied. Significant shifts in the dynamics of the investigated parameters were observed in diseases of HBS, with more pronounced changes occurring in the saliva. The presence of the detected changes in the examined individuals in the plasma and in the saliva of the studied parameters testify to the advisability of studying saliva in diseases of HBS and the prospects of using saliva as an object for early diagnosis.